What would Jesus read? : popular religious books and everyday life in twentieth-century America - Smith, Erin A. (Erin Ann), 1970- (The University of North Carolina Press, 2015)
Since the late 19th century, religiously themed books in America have been commercially popular yet scorned by critics. Working at the intersection of literary history, lived religion and consumer culture, Erin A. Smith considers the largely unexplored world of popular religious books, examining the apparent tension between economic and religious imperatives for authors, publishers and readers.